Pendugaan Aksi Gen Kandungan Na, K dan Klorofil untuk Adaptasi Tanaman Kedelai terhadap Salinitas - Fachrina Wibowo; Armaniar Armaniar (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2019)
Salinity area experienced expansion that caused be contamination of irrigation water,sea water intrusion, drought stress and excessive uses of fertilizers.varieties is one of the plant breeding program to resolve salinity problem, before that however breeder must know plant adaptation mechanism in morphology, physiology and biochemical so that plant can be catagorized adapt and as having potential for the tolerant varieties. This writing aim to know the action gen estimation through skewness and kurtosis patern Na, K and chlorophyll content, so it is know if plant able to adapt with salinity. This research used a destructive analysis. (A) Anjasmoro varieties, (G) Grobogan varieties, (N) Grobogan varieties that have been through repeated selection as comparison. Research result show the tolerant varieties having high K+ ion, less Na+ and high chlorophyll content.